Outcome of the Pesticides Peer Review Meeting on general recurring issues in ecotoxicology. Issue 7 (8th July 2019) - ; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Chaideftou, Eugenia; Ctverackova, Lucie; De Lentdecker, Chloe; Ippolito, Alessio; Kardassi, Dimitra; Lythgo, Chris; Molnar, Tunde; Padovani, Laura; et al.
Abstract : This technical report reflects the outcome of the ecotoxicology experts meeting on general recurring issues noted during the EFSA peer reviews of pesticide active substances under Regulation (EC) No 1107/2009. General and specific issues were identified and discussed relating to risk assessment for birds and mammals, aquatic organisms, non‐target arthropods and soil organisms. Conclusions and recommendations on these topics were drawn.